Common idiopathic pulmonary fibrosis risk variants are associated with hypersensitivity pneumonitis. Issue 5 (7th January 2022) - Furusawa, Haruhiko; Peljto, Anna L; Walts, Avram D; Cardwell, Jonathan; Molyneaux, Philip L; Lee, Joyce S; Fernández Pérez, Evans R; Wolters, Paul J; Yang, Ivana V; Schwartz, David A
Abstract : A subset of patients with hypersensitivity pneumonitis (HP) develop lung fibrosis that is clinically similar to idiopathic pulmonary fibrosis (IPF). To address the aetiological determinants of fibrotic HP, we investigated whether the common IPF genetic risk variants were also relevant in study subjects with fibrotic HP. Our findings indicate that common genetic variants in TERC, DSP, MUC5B and IVD were significantly associated with fibrotic HP. These findings provide support for a shared etiology and pathogenesis between fibrotic HP and IPF.